Home literacy in the digital era: The role of mobile screen media frequency in a U.S. state. (26th July 2022) - Turco, Rosa G.; Lesaux, Nonie K.; Jones, Stephanie M.
Abstract: Studies suggest that mobile screen media can play a positive role in young children's language and literacy development. However, the role of mobile screen media in the home literacy environment of pre‐school aged children has not been widely explored. Currently, it is unclear whether the amount of time on mobile devices has any association with their language and literacy development. The present study therefore explored the frequency of mobile digital media use and its relationship to children's language and emergent literacy skills, and whether and how child and family characteristics may have mediated this relationship. The sample consisted of 881 children in Massachusetts ( M age  = 5.16; 69% White, non‐Hispanic; 48% female) who completed language and literacy assessments on letter/word recognition, phonological awareness, vocabulary, syntax and language. Parents completed a survey on their child's literacy and technology activities at home. Results suggest that any associations between mobile screen media and language and literacy development may not be explained by quantity of use, but rather the nature of use. No robust statistically significant associations were found between the frequency of mobile media device use and children's language and literacy skills after controlling for key child and family background characteristics. Although rhyme awareness scores were significantly related to frequency of mobile device use, the association was weak. Thus, further research should explore types of activities, app features, and interactions that are important for children's development of language and literacy skills when using mobile media devices. Practitioner notes: What is already known about this topic Pre‐school aged children are spending an increasing amount of time with mobile screens. Mobile screen media can play a positive role in young children's language and literacy development. What this paper adds This paper describes the frequency in which pre‐school children in one US state use mobile screen media. The results of this paper provide suggest that there are no associations between mobile screen media and language and literacy development. This paper discusses how several home environmental factors play a role in children's early development of language and literacy. Implications for practice and/or policy Practitioners and teachers working with families of pre‐school children can focus on supporting the quality of interactions children have with mobile media rather than focusing on limiting the amount of time children spend with mobile media. Parents, practitioners and teachers should become familiar with educational media available and learn about effective ways to use it especially among children from low‐income household who engage with mobile media at higher rates.